Fuzzy Version of Secant Method to Solve Fuzzy Non-Linear Equations - Saha, Goutam Kumar; Shirin, Shapla (GANIT: Journal of Bangladesh Mathematical Society, 2016)
In this paper fuzzy version of secant method has been introduced to obtain approximate solutions of a fuzzy non-linear equation. Graphical representations of the approximate solutions have also been shown. The idea of converging to the root to the desired degree of accuracy, which is the optimum solution, of a fuzzy non-linear equation has been focused. GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 127-134